C♯ for financial markets - Duffy, Daniel J. (John Wiley & Sons, 2013)
In this step-by-step guide to software development for financial analysts, traders, developers and quants, the authors show both novice and experienced practitioners how to develop robust and accurate pricing models and employ them in real environments.